2007
DOI: 10.1002/chp.119
|View full text |Cite
|
Sign up to set email alerts
|

International medical graduates: Learning for practice in Alberta, Canada

Abstract: Settling into Alberta, Canada, physicians accommodated and adjusted to their settings with learning activities related to the clinical problems and situations that presented themselves. Collegial support in host communities appeared to be a critical dimension in how well physicians adjusted. The results suggest that mentoring programs may be a way of facilitating settlement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 8 publications
1
36
1
Order By: Relevance
“…The setting is unique (Lockyer et al 2007;Klein et al 2009). The rural communities are small and may only have 2-4 other physicians.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The setting is unique (Lockyer et al 2007;Klein et al 2009). The rural communities are small and may only have 2-4 other physicians.…”
Section: Resultsmentioning
confidence: 99%
“…system expectations (Lockyer et al 2007). The ways that the people earn their living and spend their leisure time are different (Klein et al 2009).…”
Section: Physician Leadermentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some local Saudi academic and health institutes have indicated that the many allied health graduates face a lot of difficulties and challenges to pass an interviews and written exam for their seeks job application. These facts have encouraged our local Saudi academic medical institutes to go through local and international accreditation programs to enable them to develop and enhance the quality of their education system (11,12) and training methodology (13,14,15) , to reduce the factors and number of program failures. And to insure that their graduates are will be capable to work successfully in all different challenged and success in their medical practice and future carriers development training programs (16,17) .…”
Section: Introductionmentioning
confidence: 99%